All Days 2011
DOI: 10.2118/141429-ms
|View full text |Cite
|
Sign up to set email alerts
|

Salt-tolerant, Thermally-stable Rheology Modifier for Oilfield Drilling Applications

Abstract: The enhanced performance of drilling fluids, especially High-Temperature, High-Pressure (HTHP) compatibility, will allow more efficient and safer drilling in challenging environments. A novel class of synthetic polymers has been developed as high performance rheology modifiers (viscosifiers) for water-based HTHP drilling fluids. The leading polymer candidate was shown to be an effective viscosifier, with excellent salt-tolerance and thermal stability compared to conventional viscosifiers used in water-based dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Wang et al [122] have suggested that an ideal viscosifier used for HPHT WBDF should possess similar rheological properties to xanthan gum, exhibiting high shear thinning properties with enhanced salt tolerance and thermal stability. For WBDF, a synthetic polymeric viscosifier has been developed which exhibits exceptional thickening efficiency, salt tolerance, and thermal stability at temperature ranges of 450-464 K in the presence of monovalent halide brines [123].…”
Section: Viscosifier Selection For Hpht Applicationmentioning
confidence: 99%
“…Wang et al [122] have suggested that an ideal viscosifier used for HPHT WBDF should possess similar rheological properties to xanthan gum, exhibiting high shear thinning properties with enhanced salt tolerance and thermal stability. For WBDF, a synthetic polymeric viscosifier has been developed which exhibits exceptional thickening efficiency, salt tolerance, and thermal stability at temperature ranges of 450-464 K in the presence of monovalent halide brines [123].…”
Section: Viscosifier Selection For Hpht Applicationmentioning
confidence: 99%
“…Due to their excellent water stability and ability to interact with oppositely charged macromolecules and surfaces, polyelectrolytes have been extensively used in various fields, from materials science and colloids to biophysics. Their predominant applications include usage in optoelectronic devices [ 14 ], solar cells [ 15 ], rheology modifiers [ 16 , 17 ], adsorbents [ 18 ], coatings [ 19 , 20 ], biomedical implants [ 21 ], colloidal stabilizers [ 22 ], suspending agents [ 23 ], and for drug delivery and pharmaceutical uses.…”
Section: Introductionmentioning
confidence: 99%